Augmented Reality Application to Efficiency the Process of Making Batik Motifs Using Vertex Marker - Kusuma, Wahyu Teja; Tolle, Herman; Supianto, Ahmad Afif (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
From the total time of making traditional Batik, the batik stage is the most time consuming because there are a lot of mistakes due to lack of carefulness when making batik motifs on cloth. To overcome the problem of making Batik motifs, this research utilizes the strengths and capabilities of Marker-Based Augmented Reality technology. The development of Marker-Based Augmented Reality applications is done by replacing digital objects with Batik motif images and markers attached to the fabric. Development of Marker-Based Augmented Reality applications using vertex markers to reproduce Batik motif objects in order to overcome the limitations of the reach of hands when making Batik motifs on fabric Finally, by using Marker-Based Augmented Reality applications batik makers do not need to draw Batik motifs in pencil on fabric because of Batik motifs directly displayed on the fabric surface by the application, so that it is expected to reduce the process time of making Batik motifs compared to making Batik motifs using traditional methods.